Travel and tourism in Britain, 1700-1914. edited by Allan Brodie. - Brodie, Allan (Routledge, 2016)
The British led the way in holidaymaking. This four-volume primary resource collection brings together a diverse range of texts on the various forms of transport used by tourists, the destinations they visited, the role of entertainments and accommodation and how these affected the way that tourism evolved over two centuries. This second volume traces the development of the spa from modest arrangements that emerged in the early modern period, to the large, thriving spa towns that existed in the nineteenth century. Documents show how spas evolved as well as the treatments they offered.